Assisted reproduction in patients with Klinefelter syndrome - Crha, Karel; Ješeta, Michal; Pilka, Radovan; Kašík, Marek; Mekiňová, Lenka; Vodička, Jan; Crha, Tomáš (Ceska gynekologie, 2022)
OBJECTIVE: The goal of this article is to present the current knowledge of Klinefelter syndrome and its impact on male reproductive function as well as the current treatment options. METHODS: PubMed/Medline, WoS and Scopus were searched for articles indexed until November 2021. TEXT: Klinefelter syndrome is a chromosomal aberration with an additional X chromosome in males. This may adversely affect testicular growth and spermatogenesis, thus resulting in male infertility. Recently, new knowledge has appeared about the treatment of male infertility. CONCLUSION: Interdisciplinary approach enables early dia-gnosis and treatment of patients with Klinefelter syndrome. Assisted reproductive technology is essential for infertility treatment in patients with Klinefelter syndrome.
Keywords: male sterility; Chromosome Aberrations; disorders of spermatogenesis; Humans; lidé; Infertility, Male; Male; genetic testing; mužská infertilita; mužské pohlaví; assisted reproduction; Klinefelterův syndrom; Spermatogenesis; chromozomální aberace; Reproductive Techniques, Assisted; Klinefelter syndrome; Klinefelter Syndrome; Aneuploidy; asistovaná reprodukce; spermatogeneze